Profil Persepsi tentang Keterampilan Kolaborasi dan Berpikir Kreatif Siswa Pada Mata Pelajaran Fisika - Prio Sigit Nugroho; Muhammad Nasir; Erviyenni Erviyenni; Muhammad Syafi’i (Postgraduate, University of Mataram, 2023)
The purpose of this study is to describe the results of identifying perceptions of 21st century skills on aspects of student’s collaboration and creative thinking skills in physics subjects according to the perceptions of students of SMP N 1 Bungaraya. This type of research is descriptive research. The respondents in this study were 20 students. The data collection instrument used in this study was a questionnaire of student’s perceptions of collaboration and creative thinking skills. Based on data analysis, perception aspect collaborations skills that have conducted are in category low. Aspects of student’s creative thinking skills in physics subjects are in the very low category according to student’s perceptions. The results obtained can be used as a reference for subsequent researchers to conduct Classroom Action Research, development research such as the development of learning media, learning modules and learning models